(untitled) (Journal of Atomic and Molecular Sciences, 2022)
The internally contracted multi-reference configuration interaction method (MRCI) with Davidson modification and the Douglas-Kroll scalar relativistic correction is used to calculate BSe^+ ion at the level of aug-cc-PVQZ basis set. The calculated electronic states, including four triple and two quintuple Λ-S states, are correlated to the dissociation limit of B^+(^1S_g)+Se(^3P_g) and B(^2P_u)+Se+(^4S_u). The states of ^3Π(II) and ^3Σ^-(II) from the dissociation limit of Se^+(^4S_u)+B(^2P_u) both have double well and spectroscopic properties are studied. Various curve crossing are revealed, which could lead to the predissociation of the X^3Π and ^5Π states and the possible predissociation pathway are analyzed. Spin-orbit coupling interaction is taken into account via the state interaction approach with the full Breit-Pauli Hamiltonian operator, which causes the entire six Λ-S states to split into 21 Ω states. This is the first time spin-orbit coupling calculation of BSe^+. The potential energy curves of the Λ-S and Ω electronic states are depicted with the aid of the avoided crossing rule between electronic states of the same symmetry. Then the spectroscopic constants of bound Λ-S and Ω states were obtained, which have never been observed in experiment.